Strategi Pemulihan UMKM Pada Masa New Normal Dan Industri 4.0 Di Desa Pulau Gambar - Risa Kartika Lubis; Nora Anisa Br. Sinulingga; R.Mahdalena Simanjorang (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Indonesia is currently treading on the industrial revolution 4.0. In its implementation, one of the government's strategies is the empowerment of Micro, Small and Medium Enterprises (MSMEs). MSMEs as a big pillar of economic support, can be seen from their large contribution to GDP. But on the other hand, MSMEs are one of the sectors most affected by the Corona Virus disease 2019 (COVID-19) pandemic causing the Indonesian economy to be so shaken. Seeing the large contribution of MSMEs to the economy, the recovery of MSMEs is one of the right steps to restore the Indonesian economy. By implementing the right strategy based on technology, Indonesia through the recovery of MSMEs can revive the economy in the new normal period while moving forward towards industry 4.0 in the long term, including the use of digital technology such as promotion on social media and registering businesses to the marketplace platform, building personal branding, innovation and product diversification to adapt people's lifestyles and consumption in the new normal, evaluation and financial records with digital accounting software, as well as registering MSMEs officially at the Cooperatives and MSMEs Service